Biochemical and Biotechnological Insights into Fungus-Plant Interactions for Enhanced Sustainable Agricultural and Industrial Processes - Giehl, Anderson; dos Santos, Angela Alves; Cadamuro, Rafael Dorighello; Tadioto, Viviani; Guterres, Iara Zanella; Prá Zuchi, Isabella Dai; Minussi, Gabriel do Amaral; Fongaro, Gislaine; Silva, Izabella Thais; Alves, Sergio Luiz (Plants (Basel), 2023)
The literature is full of studies reporting environmental and health issues related to using traditional pesticides in food production and storage. Fortunately, alternatives have arisen in the last few decades, showing that organic agriculture is possible and economically feasible. And in this scenario, fungi may be helpful. In the natural environment, when associated with plants, these microorganisms offer plant-growth-promoting molecules, facilitate plant nutrient uptake, and antagonize phytopathogens. It is true that fungi can also be phytopathogenic, but even they can benefit agriculture in some way—since pathogenicity is species-specific, these fungi are shown to be useful against weeds (as bioherbicides). Finally, plant-associated yeasts and molds are natural biofactories, and the metabolites they produce while dwelling in leaves, flowers, roots, or the rhizosphere have the potential to be employed in different industrial activities. By addressing all these subjects, this manuscript comprehensively reviews the biotechnological uses of plant-associated fungi and, in addition, aims to sensitize academics, researchers, and investors to new alternatives for healthier and more environmentally friendly production processes.